Effect of ZrO2 content on properties of Cu-ZrO2 nanocomposites synthesized by optimized high energy ball milling. Issue 2 (1st February 2019) - Fathy, A.; Wagih, A.; Abu-Oqail, A.
Abstract: In this paper, copper matrix nanocomposites reinforced by 5, 10 and 15 wt% ZrO2 particles were produced using high energy ball milling technique with different milling time. The optimum milling time is predicted analytically and validated experimentally. The effect of ZrO2 content on the morphology, microstructure, microhardness, compressive, electrical and wear properties of Cu-ZrO2 nanocomposites has been investigated. The results revealed that the optimum milling time to produce Cu-ZrO2 nanocomposite with homogenous distribution of reinforcement is 15 h. The compressive strength, the microhardness and wear rate of the Cu-15%ZrO2 nanocomposites are improved by 58.2%, 288% and 19.3%, respectively, compared to pure copper. However, density and electrical conductivity are negatively affected by increasing ZrO2 content. The improvement in the mechanical and wear properties comes from the large reduction of the crystallite size by increasing ZrO2, reaching 32.5, 15.2 and 11.1 nm for samples containing, 5, 10 and 15 wt% ZrO2 . Moreover, the reduction in the particle size due to mechanical milling plays a critical role in the improvement of these properties.